2015
DOI: 10.1182/blood.v126.23.5406.5406
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Infusion Rate on the Early Engraftment Following Allogeneic Intra Bone Marrow Infusion of Hematopoietic Stem Cells in a Canine DLA-Identical Reduced Intensity Transplantation Model

Abstract: Introduction: Direct intra bonemarrow (IBM) infusion of hematopoietic stem cells (HSC) is assumed to improve the homing efficiency and to accelerate the early engraftment in comparison to the conventional intravenous application of HSC. Especially for transplantation of low cell numbers i.e. "weak grafts" that is generally associated with delayed engraftment. The direct infusion of HSC in close proximity to the HSC niche by intra bone marrow transplantation (IBMT) might be a promising way. Whether the HSC infu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Graft-versus-Host Disease (GVHD) is also possible in dogs. Schaefer et al [90] reported a case in which a dog underwent reduced-intensity hematopoietic stem cell transplantation from a leukocyte antigen-identical littermate, resulting in GVHD that ultimately led to euthanasia at day 52 [90]. These adverse events may be associated with unintended immune reactions and should be carefully observed and monitored in future studies.…”
Section: Adverse Eventsmentioning
confidence: 99%
“…Graft-versus-Host Disease (GVHD) is also possible in dogs. Schaefer et al [90] reported a case in which a dog underwent reduced-intensity hematopoietic stem cell transplantation from a leukocyte antigen-identical littermate, resulting in GVHD that ultimately led to euthanasia at day 52 [90]. These adverse events may be associated with unintended immune reactions and should be carefully observed and monitored in future studies.…”
Section: Adverse Eventsmentioning
confidence: 99%